Reflection politics of Hamid Karzai in the press and other media of Afghanistan - - Ezatullah Husaini (RUDN Journal of Studies in Literature and Journalism, 2012)
Since the release of the first newspaper in 1873, a nearly 140 year period in the press in Afghanistan has changed dramatically. Never before have the freedom of the press and the media had not reached such a scale as the fall of the Taliban regime, during the presidency of Hamid Karzai. For Afghan media have a special significance. This article analyzes the coverage in the press and other media policy Karzai, identifies factors affecting the media and the media. Also considered such phenomena as the formation of a portrait of Hamid Karzai in the media, the impact of the international community and the media coverage of the role of foreign organizations in Afghanistan.